FREIGHT-HANDLING TECHNOLOGIES AND INDUSTRIAL BUILDING DESIGN: FREIGHTHOUSE AND WAREHOUSE FACILITIES OF THE CHICAGO JUNCTION RAILWAY, 1900–30. (November 2014) - Allison, Tim
<x content-type="archive" xml:space="preserve">Abstract</x> Among the first US railway companies to use the electric tractor and elevator in freight-handling buildings, the Chicago Junction Railway (CJR) primarily served industries in the rapidly growing Central Manufacturing District. CJR freight-handling services were initially provided in single-storey, and subsequently multi-storey, brick and mill buildings, using hand trucks, with only limited storage and warehousing space available. Labour cost savings, and changes in the scale and flexibility of freighthouse operations, possible with the electric tractor and elevator, allowed the CJR to meet the demand for increased freight-handling and warehousing capacity by augmenting older facilities with multi-storey, integrated freighthouse and warehouse buildings, latterly built with steel-reinforced concrete.